Long-Term Follow-up of Fixation Patterns in Eyes With Central Scotomas From Geographic Atrophy That Is Associated With Age-Related Macular Degeneration - Sunness, Janet S. (2005)
PURPOSE: To study whether fixation patterns changed over time in patients with central scotomas from geographic atrophy from age-related macular degeneration. DESIGN: Prospective cohort study. METHODS: SETTING: Institutional. PATIENT OR STUDY POPULATION: Prospective natural history study of geographic atrophy included 34 eyes of 25 patients with baseline acuity between 20/80 and 20/200 and with subsequent follow-up. OBSERVATION PROCEDURES: Baseline and annual follow-up visits included best-corrected visual acuity, scanning laser ophthalmoscope macular perimetry, reading rate, and clinical evaluation. MAIN OUTCOME MEASURES: Location of eccentric preferred retinal locus for fixation (PRL). RESULTS: At baseline, 77% of study eyes had a PRL. At the final visit (median follow-up, 5.3 years), 91% of study eyes had a PRL, with 81% of the eyes retaining the baseline PRL location. Fixation with the scotoma to the right and fixation with the scotoma superior were the first and second most common fixation patterns, respectively. Reading rates of <50 words/min were present in 54% of eyes. Eyes fixating with the scotoma to the left tended to have lower reading rates than eyes fixating with right or superior patterns. CONCLUSION: Fixation with right pattern remained the most common fixation pattern, both in patients with a PRL at baseline and in patients who had a PRL during follow-up. Eyes with a PRL at baseline generally retained this pattern. The reading rate data suggest an advantage of fixation with right or superior pattern, rather than left. Reading rate declined further during follow-up in most patients.